1998
DOI: 10.4269/ajtmh.1998.59.231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rhinosporidiosis of the eye and its adnexa in Nepal.

Abstract: This study describes the clinical features, diagnosis, and treatment of rhinosporidiosis of the eye and its adnexa in a series of 76 cases in Nepal and six originating in India. The disease caused by the fungus Rhinosporidium seeberi was seen most frequently in young children between eight and 10 years of age. Males were infected more than females (2.5:1). The conjunctiva was the most common site of infection in 76 (92.68%) of the cases. The lacrimal sac was affected only in six (7.32%) cases. Simple total exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 6 publications
1
61
0
1
Order By: Relevance
“…Rhinosporidioisis appears to be endemic in the Indian subcontinent (54,199,258,352), but significant numbers of cases have also been reported from Malawi and Kenya (295), northern Serbia (413), Zaire (397), Kuwait (371), and the United States of America (108,169,321). The prevalence of this condition in a south Indian village was reported to be 470 per 100,000 population (61).…”
Section: Mycotic Conjunctivitismentioning
confidence: 99%
See 3 more Smart Citations
“…Rhinosporidioisis appears to be endemic in the Indian subcontinent (54,199,258,352), but significant numbers of cases have also been reported from Malawi and Kenya (295), northern Serbia (413), Zaire (397), Kuwait (371), and the United States of America (108,169,321). The prevalence of this condition in a south Indian village was reported to be 470 per 100,000 population (61).…”
Section: Mycotic Conjunctivitismentioning
confidence: 99%
“…The prevalence of this condition in a south Indian village was reported to be 470 per 100,000 population (61). Children and young adults (up to 30 years of age) living in rural areas, who work in rice fields or bathe in stagnant water, appear to be the most severely affected (61,258,284,295,352,413). Most studies have reported a male preponderance, but one study 764 THOMAS CLIN.…”
Section: Mycotic Conjunctivitismentioning
confidence: 99%
See 2 more Smart Citations
“…El tratamiento de este cuadro considera la resección completa de la lesión 3,14,15 ; la cual puede ser combinada con crioterapia o cauterización del lecho para evitar recurrencias, aunque se han reportado casos con regresión espontánea 16 .…”
Section: Discussionunclassified